Ascorbic acid can alleviate the degradation of levodopa and carbidopa induced by magnesium oxide. Issue 7 (17th June 2022) - Miyaue, Noriyuki; Kubo, Madoka; Nagai, Masahiro
Abstract: Introduction: Levodopa and carbidopa are reported to be degraded by magnesium oxide (MgO), which is often used as a laxative for patients with Parkinson's disease (PD). Ascorbic acid (AsA) can stabilize levodopa and carbidopa solutions; however, the effect of AsA on the degradation of levodopa and carbidopa induced by MgO has not been fully investigated. Methods: The effect of AsA was evaluated using in vitro examinations, compared with lemon juice, and by measuring the plasma concentration of levodopa in a patient with PD. Results: In vitro experiments showed that the relative concentrations of levodopa remained almost constant, and the relative concentrations of carbidopa decreased with time with addition of MgO. AsA mitigated this effect in a concentration‐dependent manner, whereas the addition of lemon juice caused little change, although the pH decreased to the same extent. The results of levodopa pharmacokinetics of the patient showed that the area under the plasma concentration‒time curve values from hour 0 to 8 were 53.00 μmol·h/L with regular administration and 67.27 μmol·h/L with co‐administration of AsA. Conclusions: AsA can mitigate the degradation of carbidopa induced by MgO and may contribute to improving the bioavailability of levodopa in patients with PD. Abstract :